Rancang bangun sistem monitoring dan kontrol smart home berbasis iot dengan integrasi artificial intelligence dan antarmuka web real-time - Andriansyah, Rafiq Alhariri (Maliki Interdisciplinary Journal, 2026)
Traditional smart home systems are frequently inflexible and restricted to basic on/off logic. Additionally, integration with contemporary web interfaces is hampered by the lack of integrated wireless connectivity in low-cost microcontrollers like the Arduino Uno. Through the use of a serial bridge to overcome connectivity issues and the integration of artificial intelligence for automated analysis, this project seeks to develop a real-time monitoring and home device control system (lights, fans, doors). The Large Language Model (Llama/Kolosal) API serves as the intelligent logic processing brain, Next.js serves as the dashboard interface, Node.js serves as the serial data transmission bridge to the web, and Arduino Uno serves as the hardware controller. According to test results, the system can show sensor data in real-time with minimal latency using the Socket.io protocol. When identifying sensor anomalies, the "Jarvis" AI assistant function accurately carried out automated corrective operations (auto-fix) and successfully replied to voice requests. The combination of AI and contemporary web technologies on basic microcontrollers has been shown to improve user interaction and energy management effectiveness in Smart Home systems.